2017
DOI: 10.1111/crj.12616
|View full text |Cite
|
Sign up to set email alerts
|

Lactate levels and pneumonia severity index are good predictors of in‐hospital mortality in pneumonia

Abstract: Introduction: Pneumonia is an inflammatory disease caused by micro-organisms. The pneumonia severity index (PSI) and CURB_65 scores are widely used to predict the mortality risk. We wanted to calculate the value of lactic acid level in predicting the mortality risk. Materials and methods:This prospective cross-sectional study performed in a third level education and research hospital. The pneumonia diagnosis was determined by symptoms, physical examination findings, and radiological findings.Results: The mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 10 publications
3
22
0
Order By: Relevance
“…Our findings are consistent with several studies demonstrating that high lactate is a marker of poor prognosis in adult pneumonia. 9,10,[15][16][17] Mortality in our study (2% and 26% in patients with admission lactate of < 2.0 and > 4.0 mmol/L, respectively) was comparable with a previous report in adults (1.5% and 22.4% for lactate levels of < 2.0 and > 4.0 mmol/L, respectively). 10 Serial lactate levels collected during hospitalization were significantly higher in those who died, consistent with previous studies evaluating lactate clearance to document treatment response.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our findings are consistent with several studies demonstrating that high lactate is a marker of poor prognosis in adult pneumonia. 9,10,[15][16][17] Mortality in our study (2% and 26% in patients with admission lactate of < 2.0 and > 4.0 mmol/L, respectively) was comparable with a previous report in adults (1.5% and 22.4% for lactate levels of < 2.0 and > 4.0 mmol/L, respectively). 10 Serial lactate levels collected during hospitalization were significantly higher in those who died, consistent with previous studies evaluating lactate clearance to document treatment response.…”
Section: Discussionsupporting
confidence: 88%
“…[9][10][11][12][13][14] Recent studies have also shown lactate to be a valuable tool for predicting the risk of mortality in adult pneumonia patients. 10,[15][16][17] The use of point-of-care lactate measurement for rapid prognosis in pediatric pneumonia patients in low-resource setting, however, has not previously been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the number of trees is sufficient, the models' error rate is low and its prediction is stable, 30 and this robust nature meets medical needs. Besides, because the highly weighted variables used herein have already been known to be important factors in previous studies, 11,33 the results are reliable to a certain degree.…”
Section: Discussionsupporting
confidence: 63%
“…Moreover, proadrenomedullin, provasopressin, neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio, atrial natriuretic peptide, cortisol, copeptin, lactate, and carbon monoxide are some of the biomarkers evaluated in previous researches. [11][12][13][14][15] Several recent studies have evaluated the associations between CAP and the oxidant and antioxidant statuses. 9,10,16,17 Reactive oxygen species (ROS) occur normally in physiological conditions, and they are counterbalanced by oxidantantioxidant mechanisms.…”
Section: Introductionmentioning
confidence: 99%